EARNINGS MANAGEMENT AND FINANCIAL PERFORMANCE BEFORE AND DURING THE CORONA VIRUS DISEASE-19 PANDEMIC - Santika, Labda Agung; Herwiyanti, Eliada (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
This research set out to ascertain the impact of profitability as measured by the ratio of return on assets (ROA), return on equity (ROE), and net profit margin (NPM) on earnings management in the tourism, restaurant, and hotel sector firm listed on Indonesian Stock Exchange for the study period of 20172020. The research sample was selected by using purposive sampling. Data analysis technique using multiple linear regression analysis and carried out by SPSS version 22 software. According to the findings, net profit margin had an impact on earnings management, while return on equity and return on assets did not affect earnings management.